2015
DOI: 10.1038/ncomms9060
|View full text |Cite
|
Sign up to set email alerts
|

Integration of carbohydrate metabolism and redox state controls dauer larva formation in Caenorhabditis elegans

Abstract: Under adverse conditions, Caenorhabditis elegans enters a diapause stage called the dauer larva. External cues signal the nuclear hormone receptor DAF-12, the activity of which is regulated by its ligands: dafachronic acids (DAs). DAs are synthesized from cholesterol, with the last synthesis step requiring NADPH, and their absence stimulates dauer formation. Here we show that NADPH levels determine dauer formation in a regulatory mechanism involving key carbohydrate and redox metabolic enzymes. Elevated trehal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 49 publications
(77 reference statements)
3
48
1
Order By: Relevance
“…More generally, it was shown that DAF-16 and the IIS pathway are at the crossroads of redox and metabolism in C. elegans (Penkov et al , 2015). This finding supports the hypothesis that there are developmental checkpoints in C. elegans in accordance with the model ‘ should I stay/should I go ’ (Murphy and Hu, 2013; Schindler and Sherwood, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, it was shown that DAF-16 and the IIS pathway are at the crossroads of redox and metabolism in C. elegans (Penkov et al , 2015). This finding supports the hypothesis that there are developmental checkpoints in C. elegans in accordance with the model ‘ should I stay/should I go ’ (Murphy and Hu, 2013; Schindler and Sherwood, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of the stimulus perception, oxidative stress response is modulated by evolutionary conserved signalling pathways in the animal kingdom (Shivers et al , 2008; van der Hoeven et al , 2011; Shore and Ruvkun, 2013; Blackwell et al , 2015; Klotz et al , 2015; Penkov et al , 2015). In a general manner, the regulation of DAF-16 and SKN-1 involves an intricate network of post-translational modifications and protein–protein interactions.…”
Section: Section Ii: Potential Key Regulators Of Oxidative Stress Resmentioning
confidence: 99%
“…79,80 Interestingly, the metabolic changes that occur with dauer formation lead to decreased NADPH levels and may also represent a mechanism to inhibit dafachonic acid biosynthesis, given that DAF-9 is NADPH dependent. 18 Specifically, the increased trehalose biosynthesis that comes with dauer formation diverts glucose-6-phosphate from the pentose phosphate pathway, a major contributor to cellular NADPH levels, thereby reducing cellular NADPH levels and indirectly inhibiting dafachronic acid biosynthesis to promote dauer formation. 18 …”
Section: Role Of the Dafachronic Acids In C Elegans And Other Nematomentioning
confidence: 99%
“…18 Specifically, the increased trehalose biosynthesis that comes with dauer formation diverts glucose-6-phosphate from the pentose phosphate pathway, a major contributor to cellular NADPH levels, thereby reducing cellular NADPH levels and indirectly inhibiting dafachronic acid biosynthesis to promote dauer formation. 18 …”
Section: Role Of the Dafachronic Acids In C Elegans And Other Nematomentioning
confidence: 99%
See 1 more Smart Citation